On the use of an inflatable rubber lip to improve the reverse thrust flow field in a variable pitch fan - Rajendran, David John; Pachidis, Vassilios (American Society of Mechanical Engineers (ASME), 2021)
The installed Variable Pitch Fan (VPF) reverse thrust flow field is obtained from the flow solution of an integrated airframe-engine-VPF research model for the complete reverser engagement regime during the aircraft landing run. The reverse thrust flow field indicates that the reverse flow out of the nacelle inlet is washed downstream by the freestream. Consequently, reverse flow enters the engine through the bypass nozzle from a 180° turn of the washed-down stream. This results in a region of separated flow at the nozzle lip that acts as a blockage to the reverse flow entry into the engine. To mitigate the blockage issue, a smooth guidance of the reverse flow into the engine can be achieved by using an inflatable rubber lip that would define a bell-mouth like geometric feature with a round radius at the nacelle exit. In nominal engine operation, the rubber lip would be stowed flush within the contours of the nacelle surface. The design space of the rubber lip is studied by considering different rounding radii and locations of the turn radius with respect to the nacelle trailing edge. It is observed that a rounding radius of 0.1x nacelle length is sufficient to reduce the blockage and increase the ingested reverse flow by 47% to 18% in the 140 to 40 knots landing speed range. The inflatable rubber lip represents a design modification that can improve VPF reverse thrust operation, in cases where an augmentation of reverse thrust capability is desired
Keywords: Variable Pitch Fan; blockage; reverse thrust; rubber lip; separation mitigation; installed flow field